The effect of non-surgical periodontal therapy on systemic immune response and blood glucose level of NIDDM patients (Medical Journal of Indonesia, 2008)
Periodontal inflammation is a periodontal disorder of high prevalence in the population. Chronic periodontitis is associated with the accumulation of plaque and calculus as local factors, and systemic factors such an diabetes mellitus (DM) and HIV infection. Cytokine, especially IL-1β as inflammatory mediator for periodontal disease, may directly stimulated iNOS (inducible nitric oxide synthase) expression and NO (nitric oxide) production by β-cells, resulting in NO-mediated β-cell damage. The leucotoxin and proteases produced by periodontal pathogens will induce chemotactic and phagocytotic defect; therefore causing decreased PMN phagocytotic function. Hyperglicemia which occurs in diabetic patients increases calcium influx to the cell, resulting in the increased cytosol’s calcium ([Ca 2+]i) level and; therefore, resulting in dysfunction of PMN and impaired PMN phagocytotic function. Advanced glycosilation endproduct in NIDDM binds to monocytes resulting in the increase of pro-inflammatory cytokines (IL-1, TNFα,) and produces activation of macrophages and osteoclasts. Hyperglicemia activates diacyl glycerol (DAG)-protein kinase C (PKC), thus increasing PGE2 and cytokine expression that induce inflammation and periodontal tissue destruction processes. Studies on the effect of scaling to remove calculus disposition on blood glucose control and cellular immune response in DM patient has never been carried out. The aim of the study was to analyze the effect of scaling as non-surgical periodontal therapy on immune response (IL-1β level and PMN phagocytotic function) and blood glucose level of type 2 diabetic patients. Subjects were diabetic patients, 60 controlled-DM (CDM) and 60 uncontrolled-DM (UCDM), in Metabolic-Endocrinology Clinic of Ciptomangunkusumo Hospital, aged 40-60 years. The subjects were divided into treatment (scaling) and control group, and cellular immune response and diabetic status, before and 6 weeks after treatment were evaluated. Statistical analysis (t test) were done using Stata 7.0 software, to compare the parameters before and after scaling in CDM and UCMD subjects. The results showed that scaling decreased IL-1β level and increased phagocytotic function significantly (P<0.05). Scaling decreased fasting and 2 hours post-prandial blood glucose levels and HbA1c level, but the decrease were not significant statistically (P>0.05), except for the decrease in HbA1c level in uncontrolled DM (P=0.00). (Med J Indones 2008; 17: 20-4) Keywords : IL-1β level, phagocytotic function, HbA1C level